Analysis of The Effect of Service Quality, Product Quality, and Price on Customer Satisfaction on CV SMART - Susanto, Susanto; Pratama, Mohammad Vicky; Pradiptya, Adhi (Economics and Business Solutions Journal, 2023)
This study aims to analyze the effect of service quality,product quality and price on customer satisfaction at Cv smart semarang.  This research was conducted using quantitative methods. The number of research samples was 96 respondents who were consumers of cv smart semarang. The technique used in this study using purposive sampling technique. Quantitative analysis results include validity test,reliability test,classic assumption test (normality test,heteroscedasticity test and multicollinearity test), multiple linear regression test and the last hypothesis test using the T test, F test and the coefficient of determination (R2).  The research results show that service quality, product quality and price have a positive and significant. With the following regression equation Y = 0,222 X1+0,284 X2+0,391 X3. And the magnitude of the coefficient of determination (R2) is 0,609 which means 60,9 percent of consumer satisfaction is influenced by service quality,product quality,and price.